Analysis Of Provision Of Types Of Complementary Foods Towards Constipation Incidence In Infants Aged 6-12 Months In Ngajum Village - Murtiani, Fitri; Shanty Natalia (Journal of Global Research in Public Health, 2016)
Complementary Food for Breast Milk (MP-ASI) is a term used for food given to toddlers which is expected to meet the nutritional needsof toddlers. However, in reality, the nutritional content of MP-ASI given to toddlers is still less than the established Adequacy Rate. The purpose of this study was to determine the relationship between the provision of complementary foods (MP ASI) and the incidence of constipation in infants aged 6-12 months in Ngajum Village, Ngajum District, Malang Regency in 2020. This study is an observational study with a cross-sectional design. The population of all toddlers aged 6-12 months with a sample of 72 respondents was selected using a simple random sampling technique. The dependent variable is the incidence of constipation and the independent variable is the provision of complementary foods. Data collection using a questionnaire and analyzed using the Chi Square test. This study shows that most mothers use instant MPASI, namely 35 respondents (48.6%) and most babies experience constipation, namely 44 respondents (61.1%). The results of statistical tests with Chi Square obtained a value of ρ = 0.000 <α = 0.05 because pvalue <α then Ho is rejected, meaning there is a relationship between the provision of types of complementary foods (MP ASI) and the incidence of constipation in infants aged 6-12 months in Ngajum Village, Ngajum District, Malang Regency. It is expected that health workers provide information to mothers regarding the types of complementary foods for breast milk (MP ASI) that are appropriate for infants aged 6-12 months. Suggestions for research respondents are to improve mothers' knowledge in caring for their babies, especially in providing MPASI, so that babies grow healthily and mothers can monitor their toddlers' growth and development optimally.